IMPLEMENTATION OF CO-WORKING SPACE IN A CAFE BUILDING WITH A MODERN ARCHITECTURE CONCEPT - Dimas, Dimas; Siregar, Hendra Fahruddin; Nuraini, Cut (Proceeding International Conference of Science Technology and Social Humanities, 2022)
The application of the co-working space concept in cafes with a modern architectural approach has become a phenomenon that has attracted attention in the context of the workplace and visitor experience. This research aims to explain how combining co-working space with a modern cafe concept can create a multifunctional environment, combining elements of work space functionality with a comfortable cafe atmosphere and attractive aesthetics. By using literature methods and direct observation of co-working work space that is integrated with a cafe, this research shows that co-working space in a modern cafe is not only a place to work, but also a place to collaborate, socialize and inspire. The interior design is carefully chosen and uses modern architectural concepts such as the use of minimalist materials, natural lighting, and flexible space to support the dynamic functionality of the space. The results of this research show that the concept of co-working space in a cafe with a modern architectural approach has a significant impact on user experience. Visitors have the opportunity to work efficiently while enjoying the cozy and inspiring atmosphere of the cafe. Technology integration, ergonomic comfort and adequate facilities are important factors in attracting user interest.